News Site Commenting Policy and Its Ethical Implications - Ika Karlina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2021)
Abstract: Internet and social media platforms have provided a voice to the readers where they can express their opinions on news articles. However, such freedom to express one’s opinion has often lead to uninhibited flow of words that can prove harmful and hurtful to a segment of people, especially when discussions revolve around race, religion, politics, and minorities. News sites have responded differently in dealing with the onslaught of negativity. Some news sites have completely closed the commenting features while a few others have moderated comment sections. Such developments have generated an ethical dilemma in the journalistic realm—trying to balance the need of free expression, and avoidance of harm. Through this study, I synthesized research that deals with commenting in the online context. I found that current policies of news outlets concerning commenting forums have not provided a conducive environment for deliberated discussion. I therefore argue that news sites should open the comment feature along while applying a policy in which commentators’ identities are non-anonymous. Furthermore, I suggest the design and implementation of a reputation strategy whereby readers can comment and engage in a dialogue on issues while exercise social rewards and punishment.